Sulfasalazine as an Immunomodulator of the Inflammatory Process during HIV-1 Infection (2019)
Background: HIV-1 induces an uncontrolled inflammatory response of several immune components, such as inflammasomes. These molecular complexes, associated with Toll-like receptor (TLR) activity, induce the maturation and release of IL-1 and IL-18 and eventually induce pyroptosis. It has been previously demonstrated that HIV induces inflammasome activation, which is significantly lower in the gastrointestinal tissue and blood from people living with HIV-1 with spontaneous control of viral replication. Therefore, immunomodulatory agents could be useful in improving HIV prognosis. Objective: To evaluate the potential inhibitory e ect of sulfasalazine (SSZ) on inflammasomes and TLRs in peripheral blood mononuclear cells (PBMCs) from people living with HIV and healthy donors. Methods: PBMCs were obtained from 15 people living with HIV and 15 healthy donors. Cells were stimulated with agonists of TLRs and inflammasomes and subsequently treated with SSZ. The concentration of IL-1 and the relative expression of NLRP3, NLRC4, NLRP1, AIM2, ASC, Caspase-1, IL-1 , and IL-18 were quantified. Results: Cells treated with SSZ exhibited a decreased IL-1 production after inflammasome and TLR stimulation, as well as regulation of inflammasome-related genes, in both people with HIV and healthy individuals. The concentration of IL-1 was positively correlated with the CD4+ T-cell count and negatively with the viral load. Conclusion: Our results suggest that SSZ has an immunomodulatory effect on inflammasome and TLR activation that depends on the clinical HIV status.